Current Topics in the Utilization of Clay in Industrial and Medical Applications - Mansoor Zoveidavianpoor (IntechOpen, 2018)
This book presents recent developments and research activities that highlight the importance of clay science and engineering in the environment and medical and civil engineering. The book contains nine chapters separated into three main sections: (1) Clay for the Environment, (2) Clay in Civil Engineering, and (3) Clay in Medical Applications. There are four chapters in the first section and the focus is made on the topics related to an introduction to the natural sources and chemical structure of one of the important clay types, montmorillonite. The application of waste recycling and the removal of arsenic and fluoride are the focus of next two chapters. In addition, a technique for corrosion protection is presented as the fourth chapter within this section. In the second section, special emphasis has been placed on the importance and application of clay in civil engineering, which is demonstrated in two chapters. In the third section, new research and development on utilizing clay minerals in medical applications is presented. Intended for readers wishing to acquire an understanding of the current trends in clay science and engineering and comprehension of the issue, this book addresses exciting topics in this field.
English
Keywords: Soil Science; Physical Sciences; Engineering and Technology; Clay Minerals; Earth and Planetary Sciences